On Orogeny and Epeirogeny in the Study of Phanerozoic and Archean Rocks - Hermes, J.; Borradaile, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1985)
Abstract The retention of the original, literal meanings of "orogeny" and "epeirogeny" is recommended. Orogeny is not a short-lived, chronostratigraphic feature nor is it a synonym for rock deformation or for widespread isotopic events. The term is applicable totectonic deformation in belts, and which produced chains of mountains in Phanerozoic (and late Proterozoic) rocks. Therefore, it maybe less appropriate in Archean rocks of the shield areas where broadly uniform isotopic events may be more appropriately considered as epeirogenetic phenomena.